Sandra Bland at the cross: A womanist reading of Mark 15:40-47 - Parker, Angela N. (2021)
How do women who lack power and privilege experience the cross? How do women who lack power and privilege view privileged men at the cross? How do such questions probe issues of Jesus’s death in the Markan passion narrative? This article employs a womanist hermeneutic of “gazing” to interpret differently the complexity of women in close proximity to death while interrogating one particular woman’s close proximity to death in contemporary memory: Sandra Bland. Particularly, a womanist hermeneutic of gazing coupled with a womanist hermeneutic of suspicion provides a liberating space for nuanced engagement with the women who gaze upon Jesus’s crucifixion from afar. Recognizing specifically that the Gospel of Mark uses the Greek word βλέπω (blepō) to identify “seeing” as a metaphor for belief, how does a womanist understanding of the Greek term θεωρέω (theōreō, which the gospel writer uses sparingly) crack open the text for contemporary audiences? Engaging issues of power, privilege, and death in relationship to the “gaze” of Mark 15:40-47, this article highlights that the women who attempt to anoint Jesus’s body in the Markan narrative, because of their gender in the highly charged testosterone environment of a militarized imperial execution, have more “skin in the game,” different from the privileged position of men in the text. What happens when women are confronted with men who exhibit high levels of masculine testosterone and masculine identity? Like Sandra Bland, they are closer to death. Accordingly, thinking through the women who go to anoint Jesus with contemporary women today means that women who are often closer to death must continue the analytical work of “gazing”, as found in Mark 15:47 to the point that returning the “gaze” produces change for those closest to death (e.g., black and brown bodies close to militarized imperial violence).
Keywords: Womanist; Sandra Bland; Mark; Atonement; #BlackLivesMatter